2023
DOI: 10.26668/businessreview/2023.v8i1.928
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the Framework of Risk Management: Policy and Hedging

Abstract: Purpose: The main purpose of this study is to evaluate different policies for managing the business risks in an effective manner.   Theoretical framework: In order to identify the hazards within the organization and evaluate several risk factors, risk management is necessary. This is a method of “analysing and evaluating” the risks, which are associated with the hazard. After making identification the risks need to analyse properly. Evaluation of the risks is based on the position and activities of the firms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Nearly two third of the companies selected were operating in Tripoli and the rest were in Benghazi. With regard to the application of risk management (RM) practices (Shakatreh, 2023) of the investigated companies, it was found that they did it either in in a formal or informal way.…”
Section: Resultsmentioning
confidence: 99%
“…Nearly two third of the companies selected were operating in Tripoli and the rest were in Benghazi. With regard to the application of risk management (RM) practices (Shakatreh, 2023) of the investigated companies, it was found that they did it either in in a formal or informal way.…”
Section: Resultsmentioning
confidence: 99%
“…With this definition, risk is the uncertainty about future losses. According to the business dictionary, risk is the probability of encountering danger from any negative incident such as injury, loss, legal liability, or any negative occurrence due to the impact of factors that cause risk from inside or outside, which can be prevented and limited by prior planning [1][2][3][4].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Basel Committee has included the issue of operational risk in the amendments to Basel II. Currently, many banks around the world have applied modern measures to manage operational risks, and used in Vietnamese commercial banks [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Stock markets in emerging countries have different characteristics and are relatively riskier than the equity markets of developed countries (Bekaert and Harvey, 1997;Tay and Gan, 2016). It has been observed that one of the key components of firms responsible for developing policies is risk management (Shakatreh et al, 2023). Many emerging countries undertook important reforms, such as financial liberalisation, beginning in the late 1980s and early 1990s.…”
Section: Author Abstract Co-occurrence Analysismentioning
confidence: 99%